Declaration on mental health in Africa: moving to implementation - Abdallah S. Daar; Marian Jacobs; Stig Wall; Johann Groenewald; Julian Eaton; Vikram Patel; Palmira dos Santos; Ashraf Kagee; Anik Gevers; Charlene Sunkel; Gail Andrews; Ingrid Daniels; et al. (Taylor & Francis Group, 2014)
Urgent action is needed to address mental health issues globally. In Africa, where mental health disorders account for a huge burden of disease and disability, and where in general less than 1% of the already small health budgets are spent on these disorders, the need for action is acute and urgent. Members of the World Health Organization, including African countries, have adopted a Comprehensive Mental Health Action Plan. Africa now has an historic opportunity to improve the mental health and wellbeing of its citizens, beginning with provision of basic mental health services and development of national mental health strategic plans (roadmaps). There is need to integrate mental health into primary health care and address stigma and violations of human rights. We advocate for inclusion of mental health into the post-2015 Sustainable Development Goals, and for the convening of a special UN General Assembly High Level Meeting on Mental Health within three years.